Determination of the aromatic hydrocarbon to total hydrocarbon ratio of mineral oil in commercial lubricants. Issue 3 (3rd March 2016) - Uematsu, Yoko; Suzuki, Kumi; Ogimoto, Mami
ABSTRACT: A method was developed to determine the aromatic hydrocarbon to total hydrocarbon ratio of mineral oil in commercial lubricants; a survey was also conducted of commercial lubricants. Hydrocarbons in lubricants were separated from the matrix components of lubricants using a silica gel solid phase extraction (SPE) column. Normal-phase liquid chromatography (NPLC) coupled with an evaporative light-scattering detector (ELSD) was used to determine the aromatic hydrocarbon to total hydrocarbon ratio. Size exclusion chromatography (SEC) coupled with a diode array detector (DAD) and a refractive index detector (RID) was used to estimate carbon numbers and the presence of aromatic hydrocarbons, which supplemented the results obtained by NPLC/ELSD. Aromatic hydrocarbons were not detected in 12 lubricants specified for use for incidental food contact, but were detected in 13 out of 22 lubricants non-specified for incidental food contact at a ratio up to 18%. They were also detected in 10 out of 12 lubricants collected at food factories at a ratio up to 13%. The centre carbon numbers of hydrocarbons in commercial lubricants were estimated to be between C16 and C50.